Electrochemical Synthesis-Dependent Photoelectrochemical Properties of Tungsten Oxide Powders - Anastasia Tsarenko; Mikhail Gorshenkov; Aleksey Yatsenko; Denis Zhigunov; Vera Butova; Vasily Kaichev; Anna Ulyankina (ChemEngineering, 2022)
A rapid, facile, and environmentally benign strategy to electrochemical oxidation of metallic tungsten under pulse alternating current in an aqueous electrolyte solution was reported. Particle size, morphology, and electronic structure of the obtained WO3 nanopowders showed strong dependence on electrolyte composition (nitric, sulfuric, and oxalic acid). The use of oxalic acid as an electrolyte provides a gram-scale synthesis of WO3 nanopowders with tungsten electrochemical oxidation rate of up to 0.31 g·cm−2·h−1 that is much higher compared to the strong acids. The materials were examined as photoanodes in photoelectrochemical reforming of organic substances under solar light. WO3 synthesized in oxalic acid is shown to exhibit excellent activity towards the photoelectrochemical reforming of glucose and ethylene glycol, with photocurrents that are nearly equal to those achieved in the presence of simple alcohol such as ethanol. This work demonstrates the promise of pulse alternating current electrosynthesis in oxalic acid as an efficient and sustainable method to produce WO3 nanopowders for photoelectrochemical applications.